PEMANFAATAN LIMBAH JEROAN IKAN TONGKOL (Euthynnus affinis) DAN RUMPUT LAUT COKLAT (Sargassum polycystum) SEBAGAI PUPUK PADAT TERHADAP PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) - Engga Noer Wildan Efendi; Jumsurizal, Jumsurizal; Amrizal, Sri Novalina (Marinade, 2022)
Abstract Solid organic fertilizer is a fertilizer that is composed of living things, such as weathering the remains of plants, animals, and humans. Solid fertilizer from tuna fish innards and seaweed is made by fermenting it for 2 weeks and then filtering it and then drying it and applying it to mustard plants. The parameters tested in this study were in the form of nitrogen, phosphorus, and potassium tests and continued by looking at the growth period of stem height, length, and leaf width on mustard plants. The best research results from the mixture of fish offal waste, seaweed and rice were found in the FP3 treatment, namely the composition of a mixture of 50% fish offal waste, 45% seaweed and 5% rice. The results of testing the value of N,P,K content showed the best test results were obtained in the FP3 treatment with a mixture composition of 50% fish offal waste, 45% seaweed and 5% rice, with a N value (6.17%), P (7270 ,10 mg/kg) K (2624.92 mg/100kg)